Marine mammal acoustics exposure analysis models used in US Navy environmental impact statements. - Wartzok, D.; Erbe, Christine; Getz, W.; Thomas, J. (Springer New York LLC, 2012)
In compliance with the Marine Mammal Protection Act (MMPA), the Navy must prepare Environmental Impact Statements (EISs) and obtain Letters of Authorization (LOAs) allowing, as defined in the MMPA, incidental “takes” of marine mammals for its training activities. The Navy has prepared these documents for each of its training ranges addressing the possible effects of noise on marine mammals. The authors were asked to determine whether two Navy models and a model developed by Science Applications International Corporation (SAIC) were designed and implemented to obtain the best unbiased estimates for the level A and level B (types I and II) takes for midfrequency active sonar (MFAS).